DNA polymorphic haplotypes on the short arm of chromosome 11 and the inheritance of type I diabetes mellitus. Issue 3 (June 1986) - Ferns, G A; Hitman, G A; Trembath, R; Williams, L; Tarn, A; Gale, E A; Galton, D J
Abstract : The linked polymorphic loci 5' to the insulin gene and 3' to the c-Harvey-ras-1 (c-Ha-ras) gene, both localised to the short arm of chromosome 11, have been studied in 14 type I diabetic pedigrees. The use of a cloned gene probe corresponding to the polymorphic locus adjacent to the insulin gene, in combination with the restriction endonuclease PvuII, has permitted an improvement in the resolution of sizes of insert at this locus. An MspI restriction fragment length polymorphism at the c-Ha-ras proto-oncogene locus (4 cM upstream from the insulin gene) was used to identify parental insulin gene related alleles unambiguously, and subsequently a pedigree analysis was performed to determine whether subclasses of inserts at this locus track with insulin dependent diabetes. Segregation analysis demonstrated no linkage between the polymorphic loci 5' to the insulin gene, nor 3' to the c-Ha-ras, and type I diabetes. However, a similar analysis confirmed an association between the HLA locus chromosome 6 and insulin dependent diabetes.